1970
DOI: 10.1017/s001667230000152x
|View full text |Cite
|
Sign up to set email alerts
|

A genetic study of cold resistance in wheat

Abstract: The variety Chinese Spring of Triticum aestivum is susceptible to cold treatment applied at the juvenile plant stage, while the variety CappelleDesprez shows resistance to such treatment. By cytological and backcross procedures single homologous pairs of chromosomes from CappelleDesprez were substituted for their homologues in Chinese Spring. Assay experiments carried out on each of the 21 possible substitution lines indicated that three chromosomes, 4D, 5D and 7A of Cappelle-Desprez • were involved in the det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 13 publications
4
21
0
Order By: Relevance
“…This multi-locus model for FTA/FTB is consistent with studies of winter wheat which concluded there was polygenic inheritance of winter hardiness [11,20,33,41,42]. Freezing tolerance was reported to be controlled by a few genes in diploid Solanum species [40].…”
Section: Fta2 Ftb2supporting
confidence: 85%
See 1 more Smart Citation
“…This multi-locus model for FTA/FTB is consistent with studies of winter wheat which concluded there was polygenic inheritance of winter hardiness [11,20,33,41,42]. Freezing tolerance was reported to be controlled by a few genes in diploid Solanum species [40].…”
Section: Fta2 Ftb2supporting
confidence: 85%
“…Studies with winter wheat have suggested polygenic inheritance of winter hardiness [ 11,13] and several chromosomes containing genes for frost resistance have been identified using monosomic [42] or chromosome substitution [20,41] lines. Segregation in a cross of diploid Solanum species suggested that nonacclimated freezing tolerance and capacity to acclimate were controlled by only a few genes [40].…”
Section: Introductionmentioning
confidence: 99%
“…Cold resistance, which is one factor contributing to winter-hardiness, has been shown to be influenced by the chromosomes of homoeologous group 5, and chromosomes 4D and 7A are also implicated in its control (Law and Jenkins, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…It is clear from previous studies that a number of chromosomes are responsible for the differences between varieties, so that frost resistance can be regarded as polygenie (LAW & JENKINS, 1970;JENKINS, 1971;SUTKA & RAJKI, 1978PUCHKOV & ZHIROV, 1978;SUTKA, 198 1, 1984a). However, a major proportion of the variation is associated with chromosomes of the homoeologous group 5.…”
Section: Introductionmentioning
confidence: 99%